Sarmiento y la nación cívica - Susana Villavicencio (Les Cahiers ALHIM)
The question about the meaning of our nation in occasion of the Bicentennial of the Independence of Argentina sends us back, despite its actuality, to consider a singular speech such as that one pronounced by Domingo Faustino Sarmiento with the aim of setting a real or mythical origin of a tradition of civic nation. The idea of “community of citizens” summarizes this figure of the nation that subscribes to the modern Republican tradition, and proposes the unity based on the respect for common law. This philosophical idea, supported by the enlightened elite in a moment of violent confrontations and endless civil conflict, has a central role in the process of national organization and the establishment of a republican government after the collapse of the colonial bond. We intend to explore the formulation of the idea of civic nation in the political discourse of Domingo F. Sarmiento. As a leading member of the enlightened elites of the nineteenth century Argentina, his speech is representative of historical self-understanding of the process that is lived in America and of the political identities that were developing.